Jesus and the Woman of Samaria (John 4:7b–15). From the Heritage of Tradition to the Mystery of Faith - Piotr Kot (The Biblical Annals, 2020)
The dialogue between Jesus and the woman of Samaria, which is related in detail by the author of the fourth gospel, focuses on the sign of Jacob’s well and the living water in its first part (4:7b–15). The climax of this section combines the well, the gift of God and the identity of Jesus. By way of allusion, Jesus leads the woman to the recognition of His person’s mystery. If readers wish to comprehend the meaning of this conduct, they cannot limit themselves only to the biblical story of the patriarch Jacob. They must consider the Targum traditions. Only thus is it possible to understand how a woman of Samaria could recognize the mystery of Jesus, a Jew. Setting the story in the cultural context sheds light on the author’s intentions behind the inclusion of the narrative of 4:1–42 in Corpus Johanneum. This is important in relation to the land of Samaria which was then inhabited by people who varied in terms of ethnicity and religion. The woman whom Jesus met at Jacob’s well is described in such a way as to represent all Samaritans: descendants of proto-Samaritans and immigrant heathens. All of them were invited to draw from the source of salvation opened up by Jesus Christ.